2005
DOI: 10.1051/parasite/2005123265
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative changes in serum cytokines profile and nitric oxide levels in patients with cystic echinococcosis

Abstract: Summary :The aim of the present study was to examine serum cytokines and nitric oxide (NO) levels in patients with cystic echinococcosis (CE). 28 patients with CE were studied and all underwent surgery. Serum levels of tumour necrosis factor-alpha (TNF-α), interleukin IL-1β, receptor of soluble IL-2R (sIL-2R), IL-6, IL-8, nitrate/nitrite, and C-reactive protein (CRP) were determined before and after induction of treatment. Data were compared with those obtained from 28 healthy volunteers. IL-6 was elevated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…In particular, IgG4 and IgE have been associated with the presence of active infection or relapsing/unresponsive infection after treatment , while levels of IgG2 were associated with cyst activity in another study . High levels of pro‐ and anti‐inflammatory cytokines are also generally reported in sera of CE patients ; however, this is not a constant finding and association with cyst stages is not clear‐cut . Similarly, results of in vitro stimulation of PBMC from infected patients generally report a predominant Th1 response in patients with inactive infection and/or responding to therapy, but results are often not clear‐cut .…”
Section: Immune Response In the Intermediate Hostmentioning
confidence: 97%
“…In particular, IgG4 and IgE have been associated with the presence of active infection or relapsing/unresponsive infection after treatment , while levels of IgG2 were associated with cyst activity in another study . High levels of pro‐ and anti‐inflammatory cytokines are also generally reported in sera of CE patients ; however, this is not a constant finding and association with cyst stages is not clear‐cut . Similarly, results of in vitro stimulation of PBMC from infected patients generally report a predominant Th1 response in patients with inactive infection and/or responding to therapy, but results are often not clear‐cut .…”
Section: Immune Response In the Intermediate Hostmentioning
confidence: 97%
“…The production of IL-10 and IL-4 appears actively induced by the parasite to favor its establishment by downregulating both effector arms Haralabidis et al 1995). High levels of circulating pro-and anti-inflammatory cytokines and higher in vitro production of a predominant Th1 response in patients with inactive infection and/or who responded to therapy are also generally reported (Bayraktar et al 2005;Chandrasekhar and Parija 2009;Mezioug and TouilBoukoffa 2009;Refik et al 2005;Rigano et al 1999b;Shan et al 2011;TouilBoukoffa et al 1997TouilBoukoffa et al , 1998. However, results and association with cyst stages are often not clear-cut (Hernandez-Pomi et al 1997;Rigano et al 1995bRigano et al , 1999aRigano et al , 2001Rigano et al , 2004Piccoli et al 2012;Tamarozzi et al 2010;Torcal et al 1996).…”
Section: Immune Response To E Granulosusmentioning
confidence: 81%
“…Studies have indicated that both type1 and type2 responses can be concurrently detected in the peripheral immunity during the chronic CE (Siracusano et al, ; W. Zhang et al, ). Type1 cytokines have been showed to direct effective immune reactions against the parasite (Mezioug & Touil‐Boukoffa, ; Refik, Mehmet, & Durmaz, ; Rigano, Profumo, Teggi, & Siracusano, ; Touil‐Boukoffa, Bauvois, Sancéau, Hamrioui, & Wietzerbin, ; Touil‐Boukoffa, Sancëau, Tayebi, & Wietzerbin, ), whereas type2 responses are associated with the host susceptibility and existence of a progressive disease (Rigano et al, , ). Moreover, IgG responses to the growing cyst are evidently dominated by IgG1 and IgG4 antibodies (W. Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%